Development of ultrafine-grained microstructure in Al-Cu-Mg alloy through equal-channel angular pressing - Anuhya D.S.; Gupta A.; Nayan N.; Murty S.V.S.N.; Manna R.; Sastry G.V.S. (My University, 2025)
Al-Cu-Mg alloys are extensively used for riveting applications in aerospace industries due to their relatively high shear strength coupled with high plasticity. The significant advantage of using V65 aluminum alloy ((Al-4Cu-0.2Mg) for rivet application also stems from its significantly slower natural aging kinetics, which gives operational flexibility to carryout riveting operation even after 4 days of solution heat treatment, in contrast to its equivalent alloy AA2024.Rivets are usually made by cold heading of wire rods. In order to form a defect free rivet head, grain size control in wire rods is essential at each and every stage of processing right from casting onwards upto the final wire drawing stage. Wire drawing is carried out at room temperature to reduce diameter as well as impart good surface finish. In the present study, different microstructures in V65 alloy bars were produced by rolling at different temperatures (room temperature to 523K) and subsequently deformed by equal channel angular pressing (ECAP) at 423K upto an equivalent strain of 7. ECAP was carried out to study the effect of initial microstructure on grain refinement and degree of deformation on the evolution of ultrafine grain structure. The refinement of V65 alloy by ECAP is significantly influenced by Initial microstructure but amount of deformation strongly affects the evolution processes as revealed by optical microscopy and transmission electron microscopy. © Published under licence by IOP Publishing Ltd.